فارسی ادبیات میں سیرت نبویﷺ کی روایت : ادبی و فکری جہات کا جائزہ: The Tradition of Prophetic Biography in Persian Literature: A Study of Literary and Intellectual Dimensions - Muhammad Safdar; Dr. Umar Hayat (Al-Amīr Research Journal for Islamic Studies, 2025)
This study explores the tradition of Sīrah Nabawiyyah (Prophetic Biography) within Persian literature, focusing on its literary manifestations and intellectual trajectories. Persian literary heritage has played a pivotal role in presenting the life of Prophet Muhammad ﷺ not only as a spiritual and religious model but also as a source of ethical, cultural, and intellectual inspiration. By examining classical and modern Persian texts, this research highlights the ways in which poets, historians, and thinkers articulated the Prophet’s personality, teachings, and universal message through diverse literary genres, including poetry, prose, and historiography. Furthermore, the study investigates the intellectual underpinnings that shaped these writings, demonstrating how Persian literary tradition contributed to the development of Islamic thought and interlinked it with broader cultural and civilizational contexts. The analysis emphasizes both the aesthetic qualities of literary expression and the depth of intellectual reflection, thereby offering a comprehensive understanding of how Persian literature has preserved, enriched, and transmitted the Prophetic tradition across centuries. Keywords: Persian Literature, Prophetic Biography, Intellectual Perspectives, Islamic Thought, Cultural Heritage